Innovative modified right brachiofemoral technique (Amber technique) in delivering stent graft in difficult aortic arch anatomy - Amber, Khalid (Journal of Contemporary Medical Sciences, 2025)
Thoracic endovascular aortic repair (TEVAR) is a less invasive alternative to open surgery for aortic arch pathologies, but extreme arch tortuosity or sharply angulated “gothic” arches can impede successful stent-graft delivery. Conventional adjunct techniques (such as brachiofemoral through-and-through guidewires or externalized transseptal wires) often provide inadequate support or carry substantial procedural risks. To address these challenges, we developed the Amber technique – a modified right brachiofemoral approach that forms a stable M-shaped guidewire loop (from femoral to right brachial access) in the ascending aorta, providing enhanced support and alignment for the endograft. We applied this technique in three patients with complex aortic arch anatomy (two with arch dissections and one with a saccular arch aneurysm). All three cases achieved successful stent-graft deployment in the intended position with acceptable procedure durations (approximately 85–97 minutes) and fluoroscopy times ( 50 minutes). No major intraoperative complications occurred; one patient experienced a delayed hemorrhagic stroke attributed to postoperative antithrombotic therapy rather than the procedure. These initial results demonstrate the feasibility of the Amber technique and suggest that its superior guidewire support and proximal stent-graft stabilization can facilitate TEVAR in severely tortuous, angulated arches. This novel approach appears to overcome limitations of conventional methods and may reduce the need for riskier adjuncts (such as transseptal wires), positioning the Amber technique as a promising innovation for safely extending TEVAR to patients with challenging aortic arch anatomy.